2008
DOI: 10.1016/j.healun.2008.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Low-flow Perfusion of Guinea Pig Isolated Hearts With 26°C Air-saturated Lifor Solution for 20 Hours Preserves Function and Metabolism

Abstract: Background-Donor human hearts cannot be preserved for >5 hours between explantation and recipient implantation. A better approach is needed to preserve transplantable hearts for longer periods, ideally at ambient conditions for transport. We tested whether Lifor solution could satisfactorily preserve guinea pig isolated hearts perfused at low flow with no added oxygen at room temperature for 20 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Consequently, determining WOOCR could be useful for quantifying organ viability even when measurements are conducted during cold preservation (4–8°C). Calculation of oxygen consumption rate (OCR) has been applied before in the study of the heart,5 the liver,6 and the kidney 7-9. It has also been shown that OCR is a reliable and useful measure of pancreatic islet quality and can be used to predict islet transplant outcome 10-12…”
mentioning
confidence: 99%
“…Consequently, determining WOOCR could be useful for quantifying organ viability even when measurements are conducted during cold preservation (4–8°C). Calculation of oxygen consumption rate (OCR) has been applied before in the study of the heart,5 the liver,6 and the kidney 7-9. It has also been shown that OCR is a reliable and useful measure of pancreatic islet quality and can be used to predict islet transplant outcome 10-12…”
mentioning
confidence: 99%
“…[11, 12] Stowe et al first evaluated Lifor in a model of low-flow perfused guinea pig hearts. Under ambient air and temperature conditions, perfusion with Lifor for 10 hours provided superior protection against cardiac injury compared to UW perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[11, 12] Recently, Lifor was shown to preserve guinea pig hearts in a coronary recirculation system for up to 20 hours and to improve renal perfusion in a porcine model of room temperature perfusion. [12, 13] However, the effect of Lifor on renal function and renal tubular epithelial survival following either warm IR injury or cold storage is unknown. Therefore, the current study aimed to compare the effectiveness of Lifor to UW solution in protecting rat kidneys from warm IR and cold storage injury and to determine the effect of Lifor on renal tubular cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular function seems better preserved after hypothermic [59][60][61] and normothermic [62,63] machine perfusion compared with SCS. Clinical trials were started in 2007 in USA (PROCEED) [64] and Europe (PROTECT) [65], with only preliminary data reported so far.…”
Section: Machine Perfusion: Experience and Devices For Clinical Usementioning
confidence: 90%